A Randomized Controlled Dose-Escalation Study of LY06006, a Recombinant Humanized Monoclonal Antibody to RANKL, in Chinese Healthy Adults - Niu, Suping; Chen, Min; Yan, Diqin; Liu, Xiangxing; Guo, Shuren; Ou, Lun; Fan, Huaying; Lv, Jie; Wang, Qian; Dong, Wenliang; Xia, Lin; Wang, Simin; et al. (Frontiers in Pharmacology, 2022)
Background: This study was conducted to explore the safety, tolerance, pharmacokinetics, pharmacodynamics, and immunogenicity of LY06006, a recombinant humanized monoclonal antibody to RANKL, when administrated subcutaneously in Chinese healthy adults. Research design and methods: This was a randomized, double-blinded, placebo-controlled, single ascending dose study performed in 32 healthy Chinese adults, who were randomly assigned to receive a single infusion dose of 18 mg, 60 mg, 120 mg study drug or placebo with a follow-up of 140-252 days. Results: No deaths or drug-related serious adverse events occurred. LY06006 was rapidly absorbed in the 60 mg group with a Tmax range of 120 h ~ 480 h and serum LY06006 concentrations decreased slowly 11-13 days after dosing with a long mean (SD) half-life of 389.58(63.44) h. The most frequent AEs were elevated serum parathyroid hormone (PTH) level (83.3%), hypocalcemia (54.2%), and hypophosphatemia (45.8%). None of the 32 subjects tested positive for anti-drug antibody during the trial. Conclusion: Single-dose subcutaneous administration of LY06006 was safe and well-tolerated in healthy Chinese adults. Cmax showed linear pharmacokinetic characteristics in the dose range of 18 mg ~ 120mg based on dose-exposure proportionality analysis. Trial registration: https://clinicaltrials.gov (Registration No. 20171459)